Chemical control of Lolium multiflorum: effect of biotype and time of spraying (Revista de Ciências Agroveterinárias, 2017)
Different herbicides were tested to control two biotypes of Lolium multiflorum, an important weed of annual and perennial crops, applied onto 3-4-leaf and pre-flowering stages. Regardless of stage and biotype, the highest efficacy (>85%) was obtained with paraquat and paraquat+diuron. Any of the tested herbicides promote effective control (>85%) of L. multiflorum when applied to 3-4-leaf plants. When applied in pre-flowering, in addition to paraquat and paraquat+diuron, only glyphosate and iodosulfuron can promote effective control (>85%), but with dependence the biotype. The herbicides paraquat and paraquat+diuron are the most recommended for the control of L. multiflorum.
Keywords: herbicides; Italian ryegrass; weed management.